Electroabsorption in InGaAs and GaAsSb p-i-n photodiodes - Liu, Y.; Jin, X.; Jung, H.; Lee, S.; Harun, F.; Ng, J. S.; Krishna, S.; David, J. P. R. (Applied physics letters, 2024)
The application of an electric field to a semiconductor can alter its absorption properties. This electroabsorption effect can have a significant impact on the quantum efficiency of detector structures. The photocurrents in bulk InGaAs and GaAsSb p-i-n photodiodes with intrinsic absorber layer thicknesses ranging from 1 to 4.8 μm have been investigated. By using phase-sensitive photocurrent measurements as a function of wavelength, the absorption coefficients as low as 1 cm−1 were extracted for electric fields up to 200 kV/cm. Our findings show that while the absorption coefficients reduce between 1500 and 1650 nm for both materials when subject to an increasing electric field, an absorption coefficient of 100 cm−1 can be obtained at a wavelength of 2 μm, well beyond the bandgap energy when they are subject to a high electric field. The results are shown to be in good agreement with theoretical models that use Airy functions to solve the absorption coefficients in a uniform electric field.